The optimal team functioning (OTF) model: A grounded theory framework to guide teamwork in curling - Collins, J.; Durand-Bush, N. (Journal of Applied Sport Psychology, 2007)
A constructivist grounded theory approach was used to investigate teamwork and team effectiveness in the sport of curling. Focus group and individual interviews were conducted with 78 athletes and 10 coaches from 19 high-performance curling teams. Data analysis led to the creation of the Optimal Team Functioning (OTF) model, which comprises 8 key components for optimal team functioning: (a) individual attributes, (b) team attributes, (c) foundational process of communication, (d) structural team processes, (e) individual regulation processes, (f) team regulation processes, (g) context, and (h) desired outcomes. Components and relationships within the model, along with practical implications, are discussed.